Ozone generation by silent electric discharge and its application in tertiary treatment of tannery effluent - Balakrishnan, P (2002)
Leather industry produces large quantities of wastewater with high pollution levels, which has to be treated before disposal. Ozone produced by silent electric discharge has been used in water treatment for disinfection and oxidation for removal of color, odor, hydrogen sulfide, iron and manganese since the early 1900s, and it is used extensively in developed countries. The use of ozone in a typical tannery effluent treatment plant in a strategic manner to maintain final BOD, COD levels within prescribed limits at all times/seasons are the theme of this paper. The different methods include pre-ozonation before anaerobic stage and in the final aerator with augmented ozonation. The basis of these techniques as applicable for typical tannery effluent treatment units is described. Ozone generation theory and their electro-chemical oxidation potential with respect to other oxidants are also shown. (C) 2002 Elsevier Science B.V. All rights reserved.